Spatial and temporal dynamics of groundwater biogeochemistry in the deep subsurface of a high-energy beach - Reckhardt, Anja; Meyer, Rena; Seibert, Stephan L.; Greskowiak, Janek; Roberts, Magali; Brick, Simone; Abarike, Grace; Amoako, Kojo; Waska, Hannelore; Schwalfenberg, Kai; Schmiedinger, Iris; Wurl, Oliver; et al. (Marine chemistry, 2024)
Intertidal sandy beach systems are considered complex biogeochemical reactors. At beach sites that are subject to high tidal and wave energy, seawater circulation can reach tens of meters deep into the subsurface and changing environmental conditions are assumed to lead to dynamic groundwater flow paths, saltwater-freshwater mixing zones, and a spatio-temporally variable groundwater biogeochemistry. Previous studies mainly focused on the upper meters of subterranean estuaries (STE), while the deep subsurface remained a black box. This study presents spatial (cross-shore) and temporal (∼ six-weekly, over 1.5 years) dynamics of the groundwater biogeochemistry that were observed down to 24 m below the ground surface (mbgs) of a sandy high-energy beach on Spiekeroog Island (Germany). In addition to redox conditions along a cross-shore transect ranging from oxic to Fe oxide reducing/slightly sulfidic, we found a previously unknown, distinct vertical redox zonation as well. Temporal variations of the biogeochemistry within low salinity groundwater at the most landward station close to the dune base were mainly driven by storm flood related seawater infiltration. Around the high water line, the extent of the upper saline plume (USP) varied over time. Furthermore, temporal dynamics of the O2 saturation at 6 mbgs indicated a seasonally shifting depth of the oxycline at this location. In the lower intertidal zone, groundwater solute concentrations displayed a temporally variable zone of deep freshwater discharge. Regarding the impact of the deep STE on the groundwater biogeochemistry of the discharge zone, our data revealed that nutrient, Mn, and Fe release along the deep flow paths through the USP towards the discharge zone was limited, likely due decreasing availability of labile organic matter and subsequent slowing down of metabolic processes with depth. High concentrations of metabolites in the upper ∼ 2 mbgs of the discharge zone were, therefore, rather attributed to the incorporation of labile organic matter during continuous and storm flood related sediment relocation and/or the contribution of older waters, e.g., the subtidal saltwater wedge. •A distinct vertical redox zonation was found down to 24 m below the subsurface.•The duneward salinity gradient was disturbed by storm surge-related flooding.•Seasonal marine organic matter supply caused a shifting deep oxycline.•Freshwater discharge was spatio-temporally variable at the lower beach.